Using individual assessments in the workplace : - Goodstein, Leonard David (Pfeiffer, 2006)
This book is the prefect resource for professionals with some background in employment assessment for selection. It offers the best expert advice available for conducting psychological assessment that will yield excellent results, both for job candidates and organizations. It will prove invaluable to anyone planning or conducting assessments for selection and development.